Image and video databases: Automatic interpretation of soccer video for highlights extraction and annotation - Assfalg, J.; Bertini, M.; Colombo, C.; del Bimbo, A.; Nunziati, W. (Proceedings of the 2003 ACM symposium on Applied computing, 2003)
Broadcasters are demonstrating interest in systems that ease the process of annotation the huge amount of live and archived video materials. Exploitation of such assets is considered a key method for the improvement of production quality, and sport videos are one of the most marketable assets. In particular, in Europe, soccer is one of the most relevant sport types. This paper deals with detection and recognition of soccer highlights, using an approach based on temporal logic models.